Media Pembelajaran Augmented Reality Dalam Meningkatkan Berpikir Kritis Dan Kreativitas Siswa Negeri 1 Sumatera Barat - Thoha, Adi; Prasetya, Febri; Yufrizal, Yufrizal; Rifelino, Rifelino (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
Due to undeveloped critical and creative thinking skills, many students do not achieve academic standards. This is indicated by grades that show that most students fail to meet the minimum completeness criteria (KKM), with a KKM score of 75. The purpose of this study is to determine how effective AR (Augmented Reality) lathe learning is on critical thinking skills and student creativity at SMK Negeri 1 West Sumatra. Quasai Experimental Design quantitative method is used in this study to determine whether or not there is a difference in the subject to be studied. To do this, researchers examine treatment differences in other subjects under controlled conditions. Based on research conducted on the results of the post-test only for critical thinking and creativity of 30 students who took part in the learning, it was found that; critical thinking of students in the application of Augmented Reality media totaling 15 students with average analysis results can be seen from the average value of critical thinking of experimental class students 80.47 and control class 73.07. Student creativity in the application of AR lathe learning media totaling 15 students with an average analysis result of 65.07% in the good category. So it can be concluded that the use of AR lathe learning media at SMK Negeri 1 West Sumatra states critical thinking and good student creativity.